Availability of Dimensions of Blue Ocean Strategy in Kolestan Company for Agricultural Instruments / Duhok - Majed M. Salih (Britain International for Academic Research (BIAR-Publisher), 2025)
The researcher seeks through the study to present and analyze blue ocean strategy and the scope of adopting its dimensions which are represented by (exclusion - reduction - increase – innovation) by company . through interviews, opinions, directions of its permanent agents as well as field monitoring to determine not only the most available dimensions to be reinforced . The study presents a theoretical and field view that can be adopted as a basement for a sound application to the dimensions of blue ocean strategy as being realistically that enables an organization to sail through blue water empty of intensive bloody competition then achieving superiority and success through meeting the needs and requirements of customers in markets that competitors find difficulty to reach them and inimitable products properties. The problem statement concentrates on causes and motives which are be formulated in a main question ( Are necessary dimensions for adopting blue ocean strategy available in the company under study? And what are the most and least available dimensions in it?) the researcher has used iterations, percentages, arithmetic mean, standard deviations and statistical laboratory (Z-test) to describe, diagnose and analyze variables of the study. The most important conclusion that the study reached is the availability of the dimensions discussed at high rates which demonstrate that the company has adopted this strategy, according to which suggestions and a mechanism for its implementation have been established in a way that enhances its uniqueness upon its competitors.